Experimental and numerical investigation of tip vortex generation and evolution on horizontal axis wind turbines. Issue 8 (28th September 2015) - Micallef, Daniel; Ferreira, Carlos Simão; Sant, Tonio; Bussel, Gerard van
Abstract: The tip vortex of a wind turbine rotor blade is the result of a distribution of aerodynamic loads and circulation over the blade tip. The current knowledge on the generation of the tip vorticity in a 3D rotating environment still lacks detailed experimental evidence, particularly for yawed flow. The aim of this paper is to investigate how circulation at the blade tip behaves and how vorticity is eventually released in the wake, for both axial and 30° yawed flow conditions through the combination of experimental and numerical simulations. Stereo particle image velocimetry is used to measure the flow field at the tip of a 2m diameter, two‐bladed rotor at the TU Delft Open Jet Facility, for both axial and yawed flow; numerical simulations of the experiments are performed using a 3D, unsteady potential flow free‐wake vortex model. The generation mechanisms of the tip vorticity are established. The spanwise circulation along the blade exhibits a similar variation in both axial and yaw cases. A comparison of the chordwise directed circulation variation along the chord between axial and yawed flow is also presented and shown to be different. The analysis is based on contour integration of the velocity field. The tip vortex trajectory for axial flow confirms previous observations on the MEXICO rotor. The experimental results for yawed conditions have clearly shown how vorticity is swept radially away from the blade under the influence of the in‐plane radial component of flow. Such phenomena were only partially captured by the numerical model. The results of this work have important implications on the modelling of blade tip corrections. Copyright © 2015 John Wiley & Sons, Ltd.